Single landmark distance-based navigation - Nguyen, Thien-Minh (2020)
In this brief, we study the distance-based navigation problem of unmanned aerial vehicles (UAVs) by using a single landmark placed at an arbitrarily unknown position. To solve the problem, we propose an integrated estimation-control scheme to simultaneously accomplishes two objectives: relative localization using only distance and odometry measurements, and navigation to the desired location under bounded control input. Asymptotic convergence is obtained by invoking the discrete-time LaSalle's invariance principle in the noise-free case, and the stability under distance measurement noise is also investigated. We also validate our theoretical findings on quadcopters equipped with ultra-wideband ranging sensors and optical flow sensors in a global positioning system (GPS)-less environment.